Operator variability in scan positioning is a major component of HR-pQCT precision error and is reduced by standardized training. Issue 1 (January 2017) - Bonaretti, S.; Vilayphiou, N.; Chan, C.; Yu, A.; Nishiyama, K.; Liu, D.; Boutroy, S.; Ghasem-Zadeh, A.; Boyd, S.; Chapurlat, R.; McKay, H.; Shane, E.; et al.
Abstract Summary In this study, we determined that operator positioning precision contributes significant measurement error in high-resolution peripheral quantitative computed tomography (HR-pQCT). Moreover, we developed software to quantify intra- and inter-operator variability and demonstrated that standard positioning training (now available as a web-based application) can significantly reduce inter-operator variability. Introduction HR-pQCT is increasingly used to assess bone quality, fracture risk, and anti-fracture interventions. The contribution of the operator has not been adequately accounted in measurement precision. Operators acquire a 2D projection ("scout view image") and define the region to be scanned by positioning a "reference line" on a standard anatomical landmark. In this study, we (i) evaluated the contribution of positioning variability to in vivo measurement precision, (ii) measured intra- and inter-operator positioning variability, and (iii) tested if custom training software led to superior reproducibility in new operators compared to experienced operators. Methods To evaluate the operator in vivo measurement precision, we compared precision errors calculated in 64 co-registered and non-co-registered scan-rescan images. To quantify operator variability, we developed software that simulates the positioning process of the scanner's software. Eight experienced operators positioned reference lines on scout view images designed to test intra- and inter-operator reproducibility. Finally, we developed modules for training and evaluation of reference line positioning. We enrolled six new operators to participate in a common training, followed by the same reproducibility experiments performed by the experienced group. Results In vivo precision errors were up to threefold greater (Tt.BMD and Ct.Th) when variability in scan positioning was included. The inter-operator precision errors were significantly greater than the short-term intra-operator precision (p  < 0.001). New trained operators achieved comparable intra-operator reproducibility to experienced operators and lower inter-operator reproducibility (p  < 0.001). Precision errors were significantly greater for the radius than for the tibia. Conclusion Operator reference line positioning contributes significantly to in vivo measurement precision and is significantly greater for multi-operator datasets. Inter-operator variability can be significantly reduced using a systematic training platform, now available online (http://webapps.radiology.ucsf.edu/refline/ ).